Share price performance surrounding share buyback event in Malaysia / Lim Keng Tee - Lim, Keng Tee (2010)
Since 1997 Asian financial crisis, companies listed in Bursa Malaysia are allowed to repurchase its share. Since then share buyback has become a common tools for the companies to signal undervaluation of share price and to sustain share price. This paper studies the CAR surrounding share buyback event over a sampling period from 2006 until 2009 for companies listed in FBM Top 100 index. The result shows that cumulative abnormal return subsequent a share buyback event is 0.26% and 0.53% for CAR (0, 2) and CAR (0, 20) respectively that signifies positive share price performance after share buyback. This paper also reaffirmed that share buyback are performed when share price is underperforming the market, where the CAR (-21,-1) is recorded at -0.44%. Market capitalization size is found to be inversely related with share price performance subsequent from share buyback event. On the other end, share price performance presented consistent increasing pattern across BTM quartile from low BTM to high BTM. This mean share price performance is direct related to the book-to-market ratio, but the regression model found to be not significant. Share buyback volume does not show particular pattern and the regression model also found that it is not significantly related to the share price performance.